Polyoxymethylene handbook : structure, properties, applications and their nanocomposites - Luftl, Sigrid, 1966-; P. M., Visakh; Sarathchandran, C., 1978- (Hoboken, New Jersey : Salem, MA : John Wiley & Sons, Scrivener Publishing, 2014)
"In recent decades, Polyoxmethylene (POM) has been positioned as a high performance engineering polymer with increasing worldwide demand, particularly in the automotive, electronics, medical, and consumer goods industries. Despite this interest in POM, there has not been a book devoted to this compound. This volume rectifies this situation by bringing together the knowledge of leading scientists from industry and academia to present research results and applications of POM, including their structure, properties, manufacture, additives, processing and applications, as well their nanocomposites and other compounds"--
"This book rectifies this situation by bringing together the knowledge of leading scientists from industry and academia to present research results and applications of POM, including their structure, properties, manufacture, additives, processing and applications, as well their nanocomposites and other compounds"--
5.3 Electrical and Electronic Industry, Fancy Goods5.4 Medical Applications; 5.5 Future Trends; References; 6 Structure and Morphology of Polyoxymethylene; 6.1 Introduction; 6.2 Crystalline Structure of POM: Orthorhombic and Hexagonal Phases; 6.3 Crystal Structure Determination; 6.4 Morphology of Orthorhombic and Hexagonal POM; 6.5 Morphology of Rubber-Modified POM; 6.6 Structure-Properties Relationships; References.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Polyoxymethylene; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Binders (Materials); Injection molding of metals; Polymers; Polyoxymethylene; Polyoxymethylene; Electronic books; Electronic books; Electronic books; Handbooks and manuals